Transient upper limb ischaemia during veno-arterial extracorporeal membrane oxygenation in a child. (17th May 2021) - Izquierdo-Blasco, Jaume; Riaza, Lucía; Pujol, Montse; Gran, Ferran; Fernández-Doblas, Joaquín; Pérez-Andreu, Joaquín; Abella, Raul F; Balcells, Joan
Abstract: Neck cannulation is the most common cannulation strategy performed to provide veno-arterial extracorporeal membrane oxygenation support in paediatric patients, especially in small children. Upper limb ischaemia is a rare complication of neck cannulation and is likely caused by arterial cannula malposition. We describe a case of right arm ischaemia caused by extrinsic compression of the right subclavian artery by the venous drainage cannula inserted through the right internal jugular vein. Upper limb hypoperfusion was resolved immediately after changing the venous drainage cannula from the right jugular vein to the right femoral vein. Abstract : Peripheral neck cannulation is a common practice in children on extracorporeal membrane oxygenation (ECMO) and has a low rate of immediate complications.